1995
DOI: 10.1038/bjc.1995.22
|View full text |Cite
|
Sign up to set email alerts
|

Multiple risk factors associated with arsenic-induced skin cancer: effects of chronic liver disease and malnutritional status

Abstract: Organization, 1980; IARC, 1987). Exposures to inorganic arsenic from medicinal (Sommers and McManus, 1953;Frost, 1967), environmental (Neubauor, 1947;Tseng et al.. 1968;Yeh et al., 1968;Yeh, 1973; Cebnran et al., 1983) and occupational (Roth, 1957;Nelson et al., 1973;Brown and Rabinowitz, 1979) sources have been found to be associated with the development of skin cancer. Blackfoot disease (BFD) is a unique peripheral vascular disorder confined to an area on the south-west coast of Taiwan (Wu et al., 1961).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(95 citation statements)
references
References 23 publications
1
91
0
3
Order By: Relevance
“…among residents of Taiwanese villages [19]. In these people, under nourishment due to a high consumption of dried sweet potato as a staple food has been found to be significantly associated with an increased prevalence of arsenic induced skin cancer.…”
Section: Number Of Patients With Clinical Symptomsmentioning
confidence: 99%
“…among residents of Taiwanese villages [19]. In these people, under nourishment due to a high consumption of dried sweet potato as a staple food has been found to be significantly associated with an increased prevalence of arsenic induced skin cancer.…”
Section: Number Of Patients With Clinical Symptomsmentioning
confidence: 99%
“…Limited studies have indicated that poor nutritional status may increase the risk of arsenic related health effects [42][43][44][45][46] . Participants with poor nutritional status (weight below 80% of the standard body weight for their age and sex) were reported form West Bangal, India to have an overall 1.6 fold increase (for male=1.5, females=2.1) in the prevalence of keratoses, suggesting that malnutrition may increase the susceptibility for arsenic toxicity 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also suggests that malnutrition was a factor in arsenic effects seen in Taiwan (Hsueh et al, 1995;Hsueh et al, 1997). Yet the largest population with relatively uniform and well documented high exposure to arsenic is in Northern Chile and is relatively well nourished , yet it has very high mortality from arsenic in water.…”
Section: Nutritionmentioning
confidence: 99%